The clinicopathological evaluation of diseases of external ear in tertiary diseases - Saini, Soumya; Sachdeva, Kavita; Sharma, Diksha; B., Anjali Krishna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: As the major part of outpatient department (OPD) comprises of diseases related to external ear, it is a need to acknowledge the topic. These diseases are sometimes seasonal and variable according to climate. Diseases may vary according to patients’ anatomy. Histopathological examination along with clinical prospective is required to remove the diseases. Advancement in radiology has made easier to determine the extension and involvement of disease. Aim of the study is to evaluate the extent of disease, its causative factors, various associations and effect of treatment. Methods: The observational cross sectional study is done on 211 patients. Detailed study is done and microscopic evaluation is done whenever required. Biopsies and pus samples taken for the histopathological and microbial examination. The data collected and entered in Microsoft excel and analysed data is presented in from of frequency and percentage shown by pie charts and tables. Results: Out of total 211 patients the commonest involved age group (56.4%) belongs to 21-40 years with 109 (51.7%) females and 102 (48.3%) males. 91% of the patients belong to lower rural socioeconomic status. Most common pathology found in my study was otomycosis in 95 (30%) cases. Other pathologies included otitis externa in 57 (27%) cases, auralmass in 33 (15.6%) cases perichondritis, keloid, preauricular sinus, pseudocystand EAC stenosis in descending order. Conclusions: Aural polyps and aral masses are found to be more intrusive. Prompt consideration of such cases should be done as they have tendency of extending intracranially.